The reuse intention of honda e-care application with an extended TAM - Alisah, Ariyani; Alfitman, Alfitman; Besra, Eri (Jurnal Mantik, 2024)
The aim of this research is to examine the reuse intention of  Honda e-Care application with an extended TAM. Reuse intention is a customer's tendency to use a company's services or certain products repeatedly in the future. The population in this study was 311 consumers of the Honda Gajah Motor Bypass, Padang City who had registered and used the Honda e-Care application in 2023. The sample was 175 consumers of the Honda Gajah Motor Bypass, Padang City who had registered and used the Honda e-Care application in 2023. 2023. The analysis method used is descriptive statistical analysis and description analysis using SmartPLS 4.0. The research results show that Habit has a positive and significant effect on the perceived usefulness and perceived ease of use of using the Honda e-Care application. System Quality has a positive and significant effect on the perceived ease of use and the perceived usefulness of using the Honda e-Care application. Perceived ease of use has a positive and significant effect on the perceived usefulness of using the Honda e-Care application. Perceived ease of use and Perceived usefulness has a positive and significant effect on consumers' reuse intention on the Honda e-Care application